SCIENTIFIC BASIS OF ADDITIONAL FOOD INTRODUCTION, STATED IN THE NATIONAL PROGRAM OF THE INFANTS FEEDING OPTIMIZATION IN THE RUSSIAN FEDERATION. PART II - V. A. Skvortsova; T. E. Borovik; O. K. Netrebko; O. L. Lukyanova; N. G. Zvonkova; N. A. Mayanskii; E. A. Kopyl'tsova; O. S. Mel’nichuk; A. A. Surganova; E. L. Semikina (Вопросы современной педиатрии)
The article contains the results of the study of clinical and biochemical blood markers of iron metabolism in infants. This study represents a part of the research, aimed to scientific confirmation of the statements associated with additional food introduction and stated in the «National program of the infants feeding optimization in the Russian Federation». In controlled conditions the children were divided into 2 main groups: feeding with breast milk and with artificial milk formulas. Each group was divided into sub-groups according to the age of the additional food introduction: 4, 5 or 6 months. The received data suggest that the iron content was appropriate in both groups at the age of 4 months before the additional food introduction; there was a gradual decrease of several values after that, especially marked in children feeding with breast milk and later introduction of additional food. The comparative analysis showed that at the age of 9 months the lowest values were in breast-fed children with additional food introduction at the age of 6 months. This can be associated not only with late additional food introduction, but also with difficulties occurring when beginning it at this age and leading to insufficient supply with certain nutrients, including iron. The detailed analysis of diets for children of different sub-groups will be discussed in the next article.